Near-equilibrium analysis of CO2 partial pressure on carbonate hydrogenation in an integrated carbon capture and utilization scheme - Iwei Wang; Zhenshan Li (Carbon Capture Science & Technology)
The integrated carbon capture and utilization (ICCU) technology, combined with the reverse water-gas shift reaction (RWGS), is considered a promising strategy for mitigating carbon emissions. This study investigates the limestone calcination and hydrogenation processes under relatively high partial pressures of CO2 in near-equilibrium conditions, at partial pressures (P) close to the equilibrium pressure (Peq), relevant to the ICCU-RWGS process, particularly during the in-situ CO2 conversion stage. The decomposition of CaCO3 during conventional calcination and hydrogenation under near-equilibrium conditions was initially examined using micro-fluidized bed thermogravimetric analysis coupled with mass spectrometry (MFB-TGA-MS) and a particle-injecting method. The results indicated that limestone decomposition during conventional calcination was inhibited under near-equilibrium conditions, with conversion near 0%. However, during the hydrogenation process, the interaction between H2 and CaCO3 further activated the decomposition of limestone. At 750 °C and P/Peq=0.9, limestone particles took ∼100 s to achieve complete conversion (100%). Given the known self-catalytic activity of CaO in converting carbonate to CO during hydrogenation, a dual-layer limestone hydrogenation process was further conducted using a fixed bed reactor. At 850 °C and a 30 vol.% H2 atmosphere, the limestone decomposition rate increased significantly and subsequently reacted with H2 to form CO, resulting in an H2/CO ratio of approximately 2.5. These findings support the viability of ICCU-RWGS approaches for future commercialization, with the product gas serving as the feedstock for the Fischer–Tropsch Synthesis (FTS) process.